The Effect of Environmental Uncertainty on Managerial Performance with Management Accounting Information Systems as an Intervening Variable (in the Indonesian State-Owned Defense Industry Sector) - Dwiky Alfarisy, Ardiansyah; Rahman, Syaiful; Handoyo, Sofik (Riviera Publishing, 2026)
The study aims to analyze the effect of environmental uncertainty on managerial performance, with management accounting information systems (MAIS) as an intervening variable in Indonesian defense industry state-owned enterprises. A quantitative explanatory survey method was employed, using questionnaires distributed to managers, with the data analyzed through path analysis to test direct and indirect effects among environmental uncertainty, MAIS, and managerial performance. The results show that environmental uncertainty has a weak and statistically insignificant direct effect on managerial performance, while MAIS also has a weak and insignificant direct effect on managerial performance (path coefficients below 0.20 and significance levels above 0.05). In addition, environmental uncertainty does not significantly influence managerial performance through MAIS as an intervening variable, indicating that MAIS does not mediate the relationship between environmental uncertainty and managerial performance in this context. These findings suggest that other organizational and managerial factors, beyond environmental uncertainty and MAIS, may play a more dominant role in shaping managerial performance in Indonesian defense industry state-owned enterprises.